Pendampingan Belajar Dengan Media Flashcard Sebagai Upaya Peningkatan Kemampuan Mengenal Huruf Hijaiyah Di TTKIT Akasia Desa Rancabungur - Fuadah, Sarah Salmatul; Azizah, Khoirun Nisa; Karimah, Syahadah Albaqiyatul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service is to describe the implementation of learning assistance using flashcard media as an effort to increase the ability to recognize hijaiyah letters at TKIT Akasia Rancabungur Village. The subjects of this research were group A students at TKIT Akasia Rancabungur Village for the academic year 2023/2024. The number of participants were 13 children. This community is carried out to determine the development of young children in knowing hijaiyah letters, especially using flashcard media. Learning is carried out using the demonstration method which will increase understanding and communication skills which can spur and stimulate increased activity and in students’ understanding.